Competition Between Chemolithotrophic Acetogenesis and Hydrogenotrophic Methanogenesis for Exogenous H2/CO2 in Anaerobically Digested Sludge: Impact of Temperature - Fu, Bo; Jin, Xin; Conrad, Ralf; Liu, Hongbo; Liu, He (Frontiers in Microbiology, 2019)
Anaerobic digestion is a widely applied technology for sewage sludge treatment. Hydrogen and CO2 are important degradation products, which serve as substrates for both hydrogenotrophic methanogenesis and chemolithotrophic acetogenesis. In order to understand the competition between these processes for H2/CO2, sludge samples were incubated under H2/CO2 headspace at different temperatures, and analyzed with respect to turnover of H2, CO2, CH4 and acetate including their δ13C values. At 15℃, 13C-depleted acetate (δ13C of −41‰ to −43‰) and transient acetate accumulation were observed under H2/CO2, and CH4 accumulated with δ13C values increasing from -53‰ to -33‰. The copy numbers of the fhs gene, which is characteristic for acetogenic bacteria, were at 15℃ one order of magnitude higher in the H2/CO2 incubations than the N2 control. At 30℃, however, acetate did not accumulate in the H2/CO2 incubation and the δ13C of CH4 was very low (−100‰ to −77‰). At 50℃, isotopically enriched acetate was transiently formed and subsequently consumed followed by the production of 13C-depleted CH4. Collectively, the results indicate a high contribution of chemolithotrophic acetogenesis to H2/CO2 utilization at 15℃ and 50℃, while H2/CO2 was mainly consumed by hydrogenotrophic methanogenesis at 30C. Fermentative production and methanogenic consumption of acetate were active at 50℃.